Predictive Value of Non-high-Density Lipoprotein Cholesterol and Neutrophil-Lymphocyte Ratio for Coronary Artery Vulnerable Plaques in Type 2 Diabetes Mellitus - Huang, Xiyi; Yang, Shaomin; Zhao, Qiang; Chen, Xinjie; Pan, Jialing; Lai, Shaofen; Ouyang, Fusheng; Deng, Lingda; Du, Yongxing; Li, Xiaohong; Hu, Qiugen; Guo, Baoliang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Patients with diabetes have an increased risk of developing vulnerable plaque (VP), in which dyslipidemia and chronic inflammation play an important role. Lately, the Non-high-density lipoprotein cholesterol (non-HDL-C) and neutrophil-lymphocyte Ratio (NLR) have emerged as potential markers of both coronary artery vulnerable plaque and cardiovascular prognosis. This study aimed to investigate the predictive value of non-HDL-C and NLR for coronary artery vulnerable plaques in patients with type 2 diabetes mellitus (T2DM). Methods: In this study, we retrospectively enrolled a total of 204 T2DM patients from January 2018 to June 2020, who underwent coronary computed tomography angiography(CCTA). The clinical characteristics were collected including age, sex, hypertension, smoking, total cholesterol, LDL-C, HDL-C, Triglyceride, non-HDL-C, HbA1c, neutrophil, lymphocyte, NLR and platelet. The multivariable logistic regression was used to estimate the association between non-HDL-C, NLR and coronary artery vulnerable plaques. Receiver operating curve（ROC） analysis was performed to evaluate the value of non-HDL-C, NLR and their combination in predicting coronary artery vulnerable plaques. Results: In our study, 67 patients (32.84%) were diagnosed with vulnerable plaque, 75 patients (36.77%) were diagnosed with non-vulnerable plaque, and 62 patients (30.39%) were diagnosed with No Plaque. Non-HDL-C and NLR have been demonstrated to be independent risk factors for coronary artery vulnerable plaque in patients with T2DM. Meanwhile, HDL-C is an independent protective factor. The AUC of non-HDL-C, NLR and their combination were 0.748(95% CI: 0.676-0.818), 0.729(95% CI: 0.650-0.800) and 0.825((95% CI: 0.757-0.887), respectively. Conclusion: Either non-HDL-C or NLR could be used as a predictor of coronary artery vulnerable plaques in T2DM patients, and the predictive efficiency and sensitivity of the combination of them would be better.